Current approaches to enhance CNS delivery of drugs across the brain barriers - Lu CT (Dove Medical Press, 2014)
Cui-Tao Lu,1 Ying-Zheng Zhao,2,3 Ho Lun Wong,4 Jun Cai,5 Lei Peng,2 Xin-Qiao Tian1 1The Second Affiliated Hospital of Wenzhou Medical University, Wenzhou City, Zhejiang Province, People’s Republic of China; 2Hainan Medical College, Haikou City, Hainan Province, People’s Republic of China; 3College of Pharmaceutical Sciences, Wenzhou Medical University, Zhejiang Province, People’s Republic of China; 4School of Pharmacy, Temple University, Philadelphia, PA, USA; 5Departments of Pediatrics and Anatomical Sciences and Neurobiology, University of Louisville School of Medicine Louisville, KY, USA Abstract: Although many agents have therapeutic potentials for central nervous system (CNS) diseases, few of these agents have been clinically used because of the brain barriers. As the protective barrier of the CNS, the blood–brain barrier and the blood–cerebrospinal fluid barrier maintain the brain microenvironment, neuronal activity, and proper functioning of the CNS. Different strategies for efficient CNS delivery have been studied. This article reviews the current approaches to open or facilitate penetration across these barriers for enhanced drug delivery to the CNS. These approaches are summarized into three broad categories: noninvasive, invasive, and miscellaneous techniques. The progresses made using these approaches are reviewed, and the associated mechanisms and problems are discussed. Keywords: drug delivery system, blood–brain barrier (BBB), central nervous system, brain-targeted therapy, cerebrospinal fluid (CSF)